Ambivalence, Gender, and Censorship in two Spanish Translations of Little Women - Giugliano, Marcello; Hernández Socas, Elia (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
In our study we analyse two Spanish translations of Louisa May Alcott’s well-known novel Little Women. The first one was published in 1948, the second in 2004, both titled Mujercitas. The choice fell to this book for several reasons. To begin, Little Women was first published in 1868–1869 and, though it was an immediate success in the USA, it was reedited and modified by the publisher and the author in 1880. The result was a softened and censored version that rounded the edges of the first edition and toned down its subversive or controversial elements, especially in relation to the image and role of women in North American society at that time. The first translation in Spain was published in 1948, appearing at a particularly dramatic moment in Spanish history, in the decade after the end of the Civil War, when censorship of foreign and home literature was particularly harsh. Mujercitas (1948) may thus be the product of a second and even third degree of censorship (the translator’s self-censorship and the institutional censorship respectively). By comparing this translation with a more recent one, which, moreover, was advertised in the Spanish publishing market as being the first Spanish translation of the original 1868–1869 source text, we attempt to identify the censored elements in the translations by focusing more specifically on the image of womanhood in the novel. The result should prompt reflections on how the ideological discourse behind the source text(s), related to the position and role of women in society, was imported and adapted to the dominant ideology in Franco’s Spain and whether such discourse has undergone significant changes in the second translation, half a century after the first one and almost thirty years after the end of the regime and of the beginning of the democratic era in Spain.